Predation on Leptodactylus marmoratus (anura: Leptodactylidae) by the spider Ctenus medius (Araneae: Ctenidae) in the Atlantic forest, southeast Brazil - Barbo, Fausto E. [UNESP]; Rodrigues, Murilo G.; Couto, Fernando M. [UNESP]; Sawaya, Ricardo J. (My University, 2009)
We report herein a case of predation by the ctenid spider Ctenus medius on a leptodactylid frog Leptodactylus marmoratus, observed in a remnant of the Atlantic Forest, municipality of São Vicente, São Paulo state, southeast Brazil. This is the first record of predation by C. medius upon L. marmoratus. Nevertheless, due to the high abundance of both groups, we suggest that the interaction between spiders and amphibians could be very common on the floor of the Atlantic Forest.
Keywords: Amphibia; Anurans; Leaf litter; Neotropical region